2009
DOI: 10.1080/02841850902735858
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative diffusion-weighted magnetic resonance imaging of normal and diseased uterine zones

Abstract: The present study shows that ADC measurements have the potential to quantitatively differentiate between normal and cancerous tissues of the uterine zones. We propose adding DWI as an adjunct sequence in the MR protocol for the assessment of uterine lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
48
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 16 publications
9
48
1
Order By: Relevance
“…Like the other reports, the present study also demonstrated a significant zonal difference of ADC values and with some of the FA values (4,5,15,19,20).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Like the other reports, the present study also demonstrated a significant zonal difference of ADC values and with some of the FA values (4,5,15,19,20).…”
Section: Discussionsupporting
confidence: 72%
“…However, the thickness and signal intensities of the myometrium and especially the endometrium change during different phases of the menstrual cycle (2,3). Depending on the histologic changes in the myometrium and endometrium, variation of the apparent diffusion coefficient (ADC) values of the normal uterine zones in the different periods of the cycle is demonstrated in the literature (4,5). Diffusion-weighted imaging (DWI) can show abnormal signals reflecting pathologic foci based on differences in molecular diffusion.…”
mentioning
confidence: 99%
“…The mean ADC value of cervical cancer lesions is lower than that of normal cervical tissue (112,(118)(119)(120)(121)(122)(123)(124)(125)(126) (123,(125)(126)(127). A prospective study of 61 patients with cervical cancer showed that all lymph nodes with a short-axis diameter larger than 5 mm were detected by DWI, regardless of whether they were benign or metastatic.…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%
“…DWI imaging of endometrial tumors has decreased ADC values (108)(109)(110)(111)(112)(113)(114)(115)(116). Endometrial carcinoma is clearly depicted as an area of increased signal intensity relative to the surrounding hypointense myometrium on DWI (116).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation